(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
This paper proposes that the system of scholarly communication and publishing must be tailored to the new technological (Internet) and social (Open Access) realities. It addresses, in particular, the need to revise and adapt the mission of academic journals so that they meet the new needs of science and society. The paper distinguishes between their research function and their institutional function and, using an example from arXiv, illustrates how these two functions may be fulfilled by subject-based repositories and scholarly journals, respectively.